Pengaruh Rasio Camel terhadap Praktik Manajemen laba di Bank Syariah - ZAHARA ZAHARA; SYLVIA VERONICA SIREGAR (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to investigate earnings management in shariah banks and the effect of CAMEL ratios on earnings management. Our samples consist of 21 shariah banks, consist of Shariah Bank (Bank Umum Syariah/BUS) dan 18 Shariah Business Unit (Unit Usaha Syariah/UUS) at years 2004-2006.Our results show that on average, there is no significant earnings management practice  (measured using discretionary accruals) in shariah banks, and CAMEL ratios do not have significant effect on earnings management, except NPM which has positive and significant effect. This indicates that although in average there is no earnings management in shariah banks, bank’s profitability encourage management to involve in earnings management activity. This study finds evidence that earnings management in BUS is significantly higher than that UUS.